1991
DOI: 10.2323/jgam.37.167
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of photosynthetic electron transport in Nostoc muscorum by Ni2+ and Ag+.

Abstract: This paper presents the inhibition of photosynthetic electron transport chain of Nostoc muscorum by divalent Ni2+ and monovalent Ag+. PS I (DCPIP/ASC-MV) and PS II (H20-*PBQ) activities were markedly inhibited by Ni2+ and Ag+ in a concentration-dependent fashion but PS II was more susceptible than PS I to Ni2+. Ago was more toxic to PS I than PS II. The greater sensitivity of PS II to Ni2+ was further confirmed by the inhibition of DCPIP photoreduction and Chl a fluorescence. Restoration of Agtinduced inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…If Ag + could penetrate plasma membrane fast, then cytotoxicity would be severe. Thus, it is hypothesized that fast penetration of Ag + across plasma membrane could affect photosynthetic electron transport and slow down primary metabolic pathways sooner [ 112 , 113 ]. Once primary metabolic pathways were slowed down, affected genes would be up- and down-regulated to allow plants to adapt into their Ag + stress.…”
Section: Discussionmentioning
confidence: 99%
“…If Ag + could penetrate plasma membrane fast, then cytotoxicity would be severe. Thus, it is hypothesized that fast penetration of Ag + across plasma membrane could affect photosynthetic electron transport and slow down primary metabolic pathways sooner [ 112 , 113 ]. Once primary metabolic pathways were slowed down, affected genes would be up- and down-regulated to allow plants to adapt into their Ag + stress.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their high degree of stress tolerance, it has been shown that cyanobacteria are highly sensitive to heavy metal pollution (Reed and Gadd 1990, De Filippis and Pallaghy 1992). Early effects of metals, such as Hg 2+ , Ni 2+ , Cu 2+ , Cr 2+ , Pb 2+ , and Ag 1+ , on the photosynthetic performance of cyanobacteria have been attributed to inhibition of the photosynthetic electron transport, mainly at the PSII reaction center (Mallick and Rai 1989, Murthy et al 1989, Singh et al 1989, 1991, Prasad et al 1991, Rai et al 1995, Lu et al 2000). In addition, it seems that a decrease in energy transfer from phycobilisomes to PSII could also contribute to inhibition of PSII activity (Murthy et al 1989, Murthy and Mohanty 1991, 1993, Prasad et al 1991, Rai et al 1995).…”
mentioning
confidence: 99%